Desenvolvimento de um sistema de aquisição de dados de baixo custo para monitoramento da integridade estrutural de pontes em estradas rurais - Brito, Daniela Seda Salgado de (2020)
The conservation of bridges on rural roads is challenging, especially for municipal bodies. Engineering can develop methods to contribute to solving this challenge through knowledge and research. A specific problem is the constant use of these works of art, which often receive no preventive maintenance programs. In most cases, pathologies are detected, and measures are taken only when the deterioration of the structure reaches a critical state or when it poses a risk to users, requiring interdiction. Knowledge of the structural behavior arising from these problems can help characterize its use and define preventive methods for its conservation. This work aimed to develop a low-cost and short-term data acquisition system for the Structural Health Monitoring (SHM) of bridges on rural roads. For this, we validated a system the laboratory and under field conditions. In the laboratory, we considered the scenario for forced and free vibration, while on the field, we only considered forced vibration. The results showed that the proposed system had low measurement errors for low frequencies when compared to commercial systems. The system errors tend to increase for frequencies above 25 Hz. The proposed system considering the frequencies and amplitudes of bridges on rural roads, can be used to monitor these structures and indicated for the establishment of maintenance programs. The system can also be employed for implementing conservation programs by the public authority.